Adjunctive Low-Dose Aspirin plus Omega-3 Fatty Acid versus Low-Dose Doxycycline on Chronic Periodontitis - Shirin Zahra Farhad; Shahram Amini; Atefeh Mahdian; Mehrdad Barkatain; Morvarid Mafi (Islamic Dental Association of Iran, 2014)
Background and Aim: Host modulation therapy (HMT) has been considered as a new modality for treatment of periodontal disease. Omega-3 fatty acid has shown inhibitory and anti-inflammatory properties in treatment of inflammatory conditions such as perio-dontitis. This study compared the efficacy of omega-3 fatty acid and low-dose aspirin with doxycycline in treatment of chronic periodontitis. Materials and Methods: Forty-five patients with chronic periodontitis were selected and their clinical periodontal parameters were measured. They received phase I of periodontal therapy and were randomly divided into three groups. Each group randomly received one of the following daily drug regimens: omega-3 fatty acid plus aspirin (80mg), doxycy-cline (20mg) and the placebo (control). Clinical parameters were measured again after six weeks. Wilcoxon test, paired t-test, Kruskal-Wallis test and one-way ANOVA were used to analyze the data. Results: The mean values of bleeding on probing (BOP), periodontal pocket depth (PPD) and clinical attachment loss (CAL) in both test groups decreased significantly compared to the placebo group (p<0.05). The reductions in the omega-3 group were significantly greater than those in the doxycycline group (p<0.05). Conclusion: Omega-3 fatty acid can improve clinical parameters of periodontal disease, even better than doxycycline, which is routinely used for HMT.